Long‐chain polyunsaturated fatty acid status in obesity: a systematic review and meta‐analysis. Issue 6 (1st April 2015) - Fekete, K.; Györei, E.; Lohner, S.; Verduci, E.; Agostoni, C.; Decsi, T.
Summary Long‐chain polyunsaturated fatty acid (LCPUFA) status has recently been related to the pathogenesis of obesity. Our aims were to systematically review observational studies investigating LCPUFA status from different blood compartments in overweight or obese subjects and to assess the relationship between LCPUFA profile and obesity. The Ovid MEDLINE, Scopus and Cochrane Library CENTRAL databases were searched from inception to January 2014. The meta‐analysis showed significant differences in the LCPUFA composition of total plasma lipids, plasma phospholipids and plasma cholesteryl esters between overweight or obese subjects and controls. Dihomo‐γ‐linolenic acid (DGLA) values were significantly higher in overweight or obese subjects compared with controls in all the investigated biomarkers. In addition, the DGLA/linoleic acid ratio (surrogate parameter for Δ6 desaturase activity) in plasma phospholipids was significantly elevated (mean difference [MD]: 0.05; 95% confidence interval [CI]: 0.02, 0.08; n = 280), while the arachidonic acid/DGLA ratio (surrogate parameter for Δ5 desaturase activity) was significantly decreased (MD: −0.55; 95% CI: −0.71, −0.39; n = 347) in overweight or obese subjects compared with controls. The results of the present meta‐analysis confirm that LCPUFA profile is altered in obesity and suggest that the differences observed in desaturase activities may be responsible for the disturbed LCPUFA metabolism in obesity.